EKONOMI DAN PERTUMBUHAN PENDIDIKAN SERTA KUALITAS HIDUP MANUSIA - Rahman, Arif (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
Economics is a science pertaining to good organization and allocation of fund resources required by both individual and group of people to fulfill their needs including educational aspect. Economy and education are closely related. Economy contributes to the high quality of education. Correspondingly, high quality of education is a kind of capital for generating skilled human resources, which are eventually able to offer added values to economy